Production of Phosphorus Fertilizers by Nitric Acid Decomposition of Central Kyzylkum Phosphorites - Hulkaroy, Abdullaeva; A., Allamuratova (Research Parks Publishing LLC, 2023)
Given that phosphorus is one of the primary macronutrients necessary for plant growth and development, the manufacturing of phosphate fertilizers is a significant element of agriculture. The Central Kyzylkum phosphorites, which are found in Central Asia, are a significant supply of phosphorus and are used to make phosphate fertilizers.